MENINGKATKAN DISIPLIN MELALUI METODE BERCERITA PADA ANAK USIA 4-5 TAHUN DI KELOMPOK BERMAIN SAYANG BUNDA DESA SRIGADING KECAMATAN LUBUK DALAM - Hartatik, Dwi; Indarto, Wusono; ', Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Based on observations in KB Sweetheart Mother of the District Srigading Lubuk In the village, the researchers found was the presence of children aged 4-5 years who arrive late to school, some children interfere with their friends while learning process, while praying always take a walk or play- play, children do not listen to the words of the teacher, the child does not obey the rules of the school and the children are not put in place the goods or toys. During this time, teachers attempt to apply discipline in children through storytelling. but in fact, the effort to bring teachers less satisfactory results. The purpose of this study was to determine the increase in the ability of Discipline at 4 -5 year olds through storytelling in KB Sweetheart Mother of the District Lubuk In Srigading village. To find out how the application of storytelling in the age of 4-5 years in KB Sweetheart Mother of the District Lubuk In Srigading village, greatly increasing the ability to know the discipline in children aged 4-5 years in KB Sweetheart Mother of the District Lubuk In Srigading village. The population in this study were children in the village Srigading KB dear Mother Lubuk In the District, totaling 14 people, which was conducted in May and April 2014. Technique if the data used is observation. Based on the results of data processing and observation of Discipline capabilities have increased each cycle. At the beginning of the cycle with the values obtained 38.69% Developing criteria yet. After the repair on the first cycle obtained a value of 70.76% with Developing criteria as expected. In the second cycle value of 88.73% was obtained with Developing criteria very well. It can be seen that through storytelling method can improve the ability of the discipline of children aged 4-5 years.Keyword : Ability increase in Discipline, Storytelling Method